Chemotherapy and salivary pH in adults with cancer: an analytical cross-sectional study at a hospital in Cajamarca, Peru - Frida Hoyos-Sagastegui (TUMI Oral Health, 2026)
Introduction: Chemotherapy may disrupt salivary gland function and alter oral acid–base balance, increasing susceptibility to dental caries, infections, and mucosal complications. Objetive: This study aimed to determine the association between chemotherapy duration and salivary pH in adults with cancer treated at a hospital in Cajamarca, Peru. Methods: An observational, analytical, cross-sectional study with prospective data collection was conducted in 68 adults selected through convenience sampling. Chemotherapy duration was obtained from oncology medical records, and the pH of unstimulated whole saliva was measured using a calibrated digital pH meter. Associations were evaluated using the chi-square test in IBM SPSS Statistics version 27, with statistical significance established at p < 0.05. Results: Acidic salivary pH was identified in 58.8% of participants, neutral pH in 35.3%, and alkaline pH in 5.9%. Chemotherapy duration was significantly associated with salivary pH (p = 0.002); acidic pH was observed in 74.3% of patients treated for 6 months or longer, compared with 15.4% of those treated for up to 1 month. In stratified analyses, the association remained significant among women (p = 0.001) and adults aged 36–50 years (p = 0.002), but not among men (p = 0.356) or participants aged 18–35 years (p = 0.907). Conclusion: Longer chemotherapy exposure was associated with greater salivary acidification, supporting the inclusion of salivary monitoring in multidisciplinary oral care for adults receiving prolonged cancer treatment.